Pengembangan Video Tutorial YouTube sebagai Media Pembelajaran Literasi Digital di SMK - Abdillah, Muhamad; Supriadi, Didi (Media Manajemen Pendidikan, 2024)
In this Era of Society 5.0, digital literacy development activities are becoming increasingly important because they are always useful in many learning activities. Currently, digital literacy learning development activities are an important need. The aim of developing vocational school-based digital literacy learning using video tutorials for a productive teacher is to develop creativity in learning methods using digital media, with the aim of making learning more relevant, effective and of course enjoyable. In accordance with the theme raised, namely the development of digital literacy learning materials using YouTube tutorial videos measuring the resistance of the Honda Beat POP FI EOT sensor (the function of the EOT sensor is to detect temperature changes in the engine). In this development, researchers used ADDIE development research methods, namely Analysis, Design, Development, Implementation and Evaluation. The benefit that can be taken is that learning can be more effective and enjoyable because students can see and listen directly to the teacher's explanations. Then, in terms of knowledge, students have an idea of ​​the practical lessons that will be carried out.